Legal Regulation of Governor's Disciplinary Powers (Comparative study) - Hamid Jasim Al-Saadi , Ayub; Baharloi , Prof.Dr. Abdullah (Basra studies journal, 2023)
The objective of this subject is to highlight the_ Governor's regulatory powers in accordance with the legal and legislative frameworks conferred upon him, which must not exceed them in order to safeguard the public interest of society and whose importance is demonstrated by his regulatory and administrative powers relating to public security, public health and public safety. This role is entrusted to the Governor, who is one of the local administrative oversight bodies whose purpose is to maintain public order and the powers conferred upon him. The Law counts the Governor, the Chief Executive Officer in his administrative unit.